(3GdEOGQI aj GdESdGe (B/s - (3GdeUQj, CMeO eMeOs ((3GdEScfOQjI(B: s (3eDSSI THGH GdLGeYI(B, s, 2004)
(3GdCQRGb hGdJLGQI,GdJLGQI aj CQV GdMLGR,adSaI GdEOGQI aj HOGjI XghQ GdESdGe,SeGJ GdEOGQI GdMchejI aj GdOhdI GdESdGejI,GdSdhc GdEOGQj aj GdESdGe,EOGQI GdehGQO GdHTQjI hTDhf GdCaQGO HGdeaghe GdGSdGej,caGAI GdEOGQI hJbjje GdCOGA,ebGQfI Hjf fXQjI GdEOGQI aj GdGSdGe hfXQjGJ GdGOGQI GdeYGUQI,GdEOGQI GdeGdjI aj GdESdGe,EOGQI GdHfhc GdGSdGejI,GdHjY aj GdefgL GdGSdGejs
(3HjHdjhZQGajG U(B.223s
Keywords: (3GbJUGOs; (3GdEOGQI (B-(3ESdGes